The physiology of physical training - Radak, Zsolt, 1961- (Academic Press, an imprint of Elsevier, 2018)
The Physiology of Physical Training provides complete coverage of the physiological and methodological aspects of physical training, providing essential knowledge for anyone involved in exercise physiology. Physiological processes at the cellular level (and for the whole organism) are covered to better explain particular training methods and convey a deeper knowledge and understanding of training techniques. Coverage of exercise training-induced adaptive responses and the most appropriate training methods to bring about targeted adaptive changes are also included. This is the perfect reference for researchers of physiology/kinesiology and human kinetics, practicing coaches, graduate students and sports medicine specialists.